Educação para o gosto: cotidiano escolar e alimentar no estado do Piauí - Negreiros, Fauston (2012)
This study assessed the education of food preferences that are constructed from curricular and everyday practices at a public school in Teresina. It examined the relationship between the curriculum, eating practices, daily school life and education about food preferences. Using an ethnographically-based methodology, the study combined qualitative and quantitative approaches. It took place in a public state school in Teresina, Piaui. Students, parents of students, teachers and school workers participated in the study, as well as residents and food sellers in the school vicinity. Data were collected by observation of the school routine, semi-structured interviews based on oral history, and a Questionnaire of Food Consumption Frequency (QFCF). Quantitative data were statistically analyzed using GraphPad Prism to estimate aspects about the education of food preferences and the different types of foods consumed. Qualitative data were examined using principles of Depth Hermeneutics, and consisted of: socio-historical analysis; formal or discursive analysis; and interpretation/reinterpretation. The results indicated that there were two dimensions of education on food preferences: the school curriculum and the concealed curriculum that is expressed in daily school life. The School Allotment, a subject that forms part of the school curriculum, encourages sensory, playful and bonding experiences with foods that are grown at school, and this strategy encourages consumption of healthy food and increases knowledge about the origin of food products. In daily school life, eating practices are particularly important: they not only provide healthy eating models in the four meals offered at the school, but they also prioritize socialization, bonding with food, are a way of practically applying the knowledge that has been acquired about food, and advocate the conscious consumption of food by the students to promote wellness through healthy eating. The identified educational dimensions are part of a formative process of the education of food preferences of students, and stimulate the consumption of vegetables and fruit (which nearly doubled during the course of a school year). There was a more than 50% reduction of weekly consumption of sugars and fried food and a substantial increase in the consumption of white meat. There was also a reduction of canned foods and a gradual minimization of the consumption of red meat, snack foods, animal organs and oils. It was clear that in order to develop the education for food preferences as a formative process that can be constructed at school, it is essential to integrate three areas: education/curriculum, food/nutrition and school environment/community.